COMMUNICATIVE DISCOURSE IN LANGUAGE LEARNING - Ochilova Noila Farmonovna (International Journal of Innovations in Engineering Research and Technology, 2021)
The dynamics of the communicative discourse is a natural process that requires an application of a wide range of skills and strategies. In particular, linguistic discourse and the interaction process have a huge impact on promoting literacy and academic skills in all students especially English language learners. The anatomy of language developmentcan help in understanding how linguistic behavior is developed and shaped later on in children’s lives. At the same time, it can be an indicator of how language and literacy develop at different stages. This awareness about the process of language developmentcan eventually help educators in providing necessary ingredients and creating conducive conditions for nurturing students’ linguistic and academic skills in schools and beyond.